2023
DOI: 10.1088/1742-6596/2442/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

Zinc ash deposition pattern and structural optimization in the continuous hot-dip galvanizing vertical furnace

Abstract: In a continuous hot-dip galvanizing vertical furnace for strip steel, zinc vapor oxidizes in the snout of the furnace to form zinc ash. The zinc ash adheres and agglomerates on the inner walls of the snout. If the zinc ash falls off and adheres to the surface of the strip, zinc ash defects will be formed, thereby affecting the surface quality of the galvanized layer. Given that the snout connects the annealing furnace and the zinc pot, the zinc ash will be transported into the annealing furnace and form nodula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Vieria et al [6] studied the particle trajectory in a galvanizing bath and found that large particles settle more quickly in the galvanizing bath, while small particles move longer before settling. Dong et al [7] found that the scheme of using baffles and exhaust ducts was the most effective in suppressing zinc ash diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Vieria et al [6] studied the particle trajectory in a galvanizing bath and found that large particles settle more quickly in the galvanizing bath, while small particles move longer before settling. Dong et al [7] found that the scheme of using baffles and exhaust ducts was the most effective in suppressing zinc ash diffusion.…”
Section: Introductionmentioning
confidence: 99%